การเสริมฤทธิ์ของส่วนสกัดจากเปลือกลำต้นสำโรง (Sterculia foetida Linn.) กับยาปฏิชีวนะในการยับยั้งการเจริญของแบคทีเรียฉวยโอกาส - ฟูเจริญไพบูลย์, ณัฐวดี; คงเจริญสุนทร, วิสาตรี; เนื่องจำนงค์, วารี (Thai Journal of Science and Technology, 2020)
Sterculia foetida Linn. is a Thai medicinal plant commonly used for healing many diseases such as skin infection, dysentery, and diarrhea. This research aimed to analyze chemical components of S. foetida extract, and to study synergistic effect of the extract against some opportunistic bacteria. From chemical analysis of bark extract from S. foetida, flavonoid, phenolic compound, phenol, terpene, steroid and sugar were found. The antioxidant activity determined by DPPH (2,2-diphenyl-1-picrylhydrazyl), of methanol extract was shown as the IC50 of 0.0086±0.0017 mg/mL. The bark extract of S. foetida showed the highest antibacterial activities against Pseudomonas aeruginosa and Klebsiella pneumoniae. In addition, the results showed that both methanol and ethanol extract from S. foetida exhibited antibacterial activities against all opportunistic bacteria (MIC values between 10-80 mg/mL). From the study of synergistic effect, the ethanol extract of S. foetida combined with ampicillin and tetracycline showed the better synergistic effect than the methanol extract against some opportunistic bacteria (FICI values between 0.03-0.5). The best times of synergistic effect against Escherichia coli ATCC 25922, K. pneumoniae, P. aeruginosa and S. aureus ATCC 25923 were in the log phase at the 2-8 hours after inoculum. The reduced MICs of antibiotics alone for killing bacteria were between 1/32 - 1/4 MICs of MICs’ alone. Also, the reduced MICs of S. foetida extract were 1/512 - 1/8 MIC of MICs’ alone. Thus, S. foetida’s extract mixed with antibiotics may be a new medicinal alternative to treat bacterial infection, and may be applied as a mixing in cosmetic products.